Surgically Induced AStigmatism of Microcoaxial Phacoemulsification Using 2.2mm Incision Compared with Conventional Phacoemulsification Using 3.2mm Incision - Bhuiyan, Md. Motahar Hossain; Huq, Deen Mohd Noorul; Sharmee, Tania Hossain (Medicine Today, 2012)
Medicine Today 2011 Volume 23 Number 01 Page 27-29 DOI: http://dx.doi.org/10.3329/medtoday.v23i1.11941